Effect of Green Betle Leaf Extract (Piper betle L.) on Indoor Microbiological Quality - Nugraheni, Ratih Mutiara; Sudaryanto, Sigid; Prasetyawati, Naris Dyah; Mulyaningsih, Tri (Poltekkes Kemenkes Tanjung Karang, 2024)
The microbiological quality of indoor air is still a signifikans concern because it causes mortality and morbidity. This study aims to analyze the effect of green betel leaf extract (Piper betle L.) on reducing the bactherial in the air. Quasi-research using the One Group Pretest Posttest design, conducted in March-May 2024. Betle leaves were extracted using the maceration method using 96% Ethanol solvent, then diluted with distilled water to obtain a concentration of 15%. Three volume variations (0.5 ml, 1.0 ml, and 1.5 ml) were put into a humidifier and applied to a nine-square-meter bedroom for three hours, with six replication. Sampling was carried out before and after the experiment. All data (N= 48) were analyzed using the One Way ANOVA and Tukey tests at CL 95%. The study results found a decrease in colonies in the treatment with a volume of 1.0 ml and 1.5 ml: 39.3% (from 36.2 to 22.3 CFU /m3) and 17.6% (from 49.2 to 37.0 CFU /m3). The treatment with a volume of 0.5 ml did not show a decrease. The statistical analysis showed a significant effect of betle leaf extract on reducing the bacteria in the air (P= 0.020). The study results have proven that green betle leaf extract can be used as a disinfectant to reduce the bacteria in the air. However, safe use must be applied by paying attention to the air humidity level.